2014
DOI: 10.1080/09540121.2014.894619
|View full text |Cite
|
Sign up to set email alerts
|

HIV-related neurocognitive impairment screening: the patient's perspective on its utility and psychological impact

Abstract: Despite ever improving advances in antiretroviral therapy, neurocognitive impairments such as asymptomatic and mild neurocognitive impairment remain a significant problem for the HIV-positive population. We distributed a post-neurocognitive impairment screening service evaluation questionnaire to assess satisfaction and anxiety. Subjects were HIV positive and aged 18-50. They were screened using the Brief Neurocognitive Score and International HIV Dementia Score as well as undergoing screening for anxiety (Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The Everyday Memory Questionnaire-Revised (EMQ-R) is a subjective measure of memory failure in everyday life, which was initially developed as a 35-item questionnaire to investigate the effects of closed-head injuries on memory performance 22 . Subsequently, this questionnaire was reduced by Royle and Lincoln 23 to a 13-item one (EMQ-R) and validated in several clinical populations, such as stroke, 24 chronic pain, 25 and human immunodeficiency virus, 26 and nonclinical populations, such as a community of younger and older adults 27 and Bosnian/Serbian healthy adults 28 . Although the item loadings were slightly different in these studies, two main factors of the EMQ-R were consistently observed with one factor relating to memory retrieval and another focusing on the attentional process, suggesting that the EMQ-R may serve as a better option to measure brain fog because of this bifactor structure ( Retrieval and Attentional ).…”
Section: Subjective Measurement Of Cognitionmentioning
confidence: 99%
“…The Everyday Memory Questionnaire-Revised (EMQ-R) is a subjective measure of memory failure in everyday life, which was initially developed as a 35-item questionnaire to investigate the effects of closed-head injuries on memory performance 22 . Subsequently, this questionnaire was reduced by Royle and Lincoln 23 to a 13-item one (EMQ-R) and validated in several clinical populations, such as stroke, 24 chronic pain, 25 and human immunodeficiency virus, 26 and nonclinical populations, such as a community of younger and older adults 27 and Bosnian/Serbian healthy adults 28 . Although the item loadings were slightly different in these studies, two main factors of the EMQ-R were consistently observed with one factor relating to memory retrieval and another focusing on the attentional process, suggesting that the EMQ-R may serve as a better option to measure brain fog because of this bifactor structure ( Retrieval and Attentional ).…”
Section: Subjective Measurement Of Cognitionmentioning
confidence: 99%
“…Another possible explanation for high NCI prevalence despite a reasonable viral suppression rate may be a history of severe immunosuppression before the commencement of treatment, a risk factor for NCI. An important biomarker of severe immunosuppression is nadir CD4 count < 200 [41].…”
Section: Clinical Factors Associated With Nci Amongmentioning
confidence: 99%
“…The Everyday Memory Questionnaire-Revised (EMQ-R) is a subjective measure of memory failure in everyday life, which was initially developed as a 35-item questionnaire to investigate the effects of closed-head injuries on memory performance. 22 Subsequently, this questionnaire was reduced by Royle and Lincoln 23 to a 13-item one (EMQ-R) and validated in several clinical populations, such as stroke 24 , chronic pain 25 and HIV 26 and non-clinical populations, such as community younger and older adults 27 , and Bosnian/Serbian healthy adults 28 . Although the item loadings were slightly different in these studies, two main factors of the EMQ-R were consistently observed with one factor relating to memory retrieval and another focusing on attentional process, suggesting that the EMQ-R may serve as a better option to measure brain fog due to this bifactor structure ( Retrieval and Attentional ).…”
Section: Introductionmentioning
confidence: 99%